CROSS-CULTURAL EFFECTS OF SENSE OF COHERENCE AND RESILIENCE ON MENTAL HEALTH IN PARKINSON'S CAREGIVERS. (16th November 2018) - Tyler, C; Lageman, S; Villasenor, T; Smith, E; Arroyo, M; Zarate, A; Avila, J; Perrin, P
Abstract: This study explored the potential effects of sense of coherence and resilience on the mental health of Parkinson's caregivers across two cultures—in Mexico and the US. Sense of coherence and resilience are known protective factors for mental health generally, but their relationship with depression and anxiety in Parkinson's caregivers has not previously been thoroughly examined. Sense of coherence includes the concepts comprehensibility (life events are understandable, explainable, and expected) and manageability (there are means to meet demands). In order to delineate possible cultural differences in the influence of sense of coherence and resilience on caregiver mental health, a multi-site survey assessing these constructs was administered to 75 Parkinson's caregivers in Mexico and 64 in the US. Four hierarchical linear regressions were run separately for participants from Mexico and the US with anxiety and depression as the criterion variables and sense of coherence and resilience as the predictors. These predictors explained 19.4% of the variance in anxiety in the US and 60.7% in Mexico; they explained 27.3% of the variance in depression in the US and 54.9% in Mexico. Within these regressions, comprehensibility was the largest unique predictor. Sense of coherence, especially comprehensibility, and resilience are influential in predicting mental health in Parkinson's caregivers, with the strongest effects in Mexico. Future studies should focus on ways to intervene on sense of coherence and resilience and the reasons for the demonstrated cultural differences in the levels of prediction for these variables.